Protótipo de um sistema de vistoria veicular através de webservices - Silva, Ilson José Sabino da (2013)
The project presents the integration of information coming from vehicular databases (made available from federal agencies, regarding legal situation of the vehicles, and which are paid by consultation) with a local database, to be installed at the vehicle inspection company, that are filled with information about the vehicle in the moment of the inspection. The registration of the data related to a particular vehicle undergoing inspection in a single base is a proper way to store the information. Besides that, when the same vehicle is again inspectioned, the data regarding its legal situation, provided by the federal vehicular databases, are already available for consultation and comparison. Companies using the developed information system, having access to the databases on vehicle registration, also have the advantage of reducing costs because instead of collecting data on paper forms for later typing in computer system, can allow direct access the database through the use of smartphones, and a digital format suitable for transmission. Another advantage is the economy of time using the remote transmission of data, eliminating the need to return to the headquarters to manual data entry. By using this service the company may also obtain advantages by not need to re-query the paid database (since each access to the data is paid!). To access data from a vehicle already consulted in a previous inspection is free of costs, since the data are still available in the local database of the company. This project was developed using the Android platform (as an app for Smartphones and Tablets), which accesses the information system and database developed through Web services using any communication network available (such as 3G or WiFi).